Heterotic-type IIA duality and degenerations of K3 surfaces - Braun, A; Watari, T (Springer Verlag, 2016)
We study the duality between four-dimensional $\mathcal{N}$ = 2 compactifications of heterotic and type IIA string theories. Via adiabatic fibration of the duality in six dimensions, type IIA string theory compactified on a K3-fibred Calabi-Yau threefold has a potential heterotic dual compactification. This adiabatic picture fails whenever the K3 fibre degenerates into multiple components over points in the base of the fibration. Guided by monodromy, we identify such degenerate K3 fibres as solitons generalizing the NS5-brane in heterotic string theory. The theory of degenerations of K3 surfaces can then be used to find which solitons can be present on the heterotic side. Similar to small instanton transitions, these solitons escort singular transitions between different Calabi-Yau threefolds. Starting from well-known examples of heterotic-type IIA duality, such transitions can take us to type IIA compactifications with unknown heterotic duals.